Histo-morphology of the alimentary canal in two freshwater snakehead fish Channa punctata and Channa striata - Mita Borman; Ismot Ara; Mohammad Kamrujjaman; Md. Rafiqun Nabi (Journal of Fisheries, 2015)
The histo-morphological study of the alimentary canal of two carnivore freshwater snakehead fish Channa punctata and C. striata was carried out from October 2013 to July 2014. It revealed that three major parts like oesophagus, stomach and intestine composed of short thick-walled body. The oesophagus begins with buccopharynx. Structure and arrangement of both villiform and canine teeth on jaws in C. striata are more extendable and stronger than C. punctata and thereby made the former one more successful predator. The availability and arrangement pattern of mucous pits and taste bud pores in oesophagus are also prominent in C. striata. The TS of stomach of both the species has broad GM devoid of goblet mucous cells,  but surface layer CC and basal layer GG open through gastric pits. The length of intestine (16.0 cm) and intestinal pyloric caeca (5.5 cm) in C. striata are larger than C. punctata (7.0 cm and 1.5 cm, respectively). However, the TS of intestinal Sr. 0.05 mm; MM. 0.8 mm; Mu 0.5 mm suggest in favour of carnivore habit of both the species.